Evaluation of peripheral muscle strength of patients hospitalized with respiratory diseases submitted to early mobilization (Research, Society and Development, 2021)
Objective: Evaluate the peripheral muscle strength of hospitalized individuals with respiratory disorders undergoing an early mobilization protocol. Methods: Sixteen hospitalized patients with pulmonary diseases were randomly randomized to the Early Mobilization (EM) group and the Early Mobilization group associated with the Cycle ergometer (EM+C). Cardiorespiratory parameters and peripheral muscle strength were evaluated before and after the intervention, through the Peg Board and Ring Test (6PBRT) and the Handgrip Strength (HGS) test. The data were expressed as (average and standard deviation) for parametric data and (median and interquartile range) for nonparametric data, using the GraphPad Prism 8.0 program, using the t-student test (paired and unpaired), Wilcoxon, one-way ANOVA and post test Tukey, Kruskal-Wallis and post test Dunn, with the significance level adopted for the statistical treatment of (p